2014
DOI: 10.1186/1471-2393-14-328
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of PMTCT services and associated factors among pregnant women attending antenatal clinics in Addis Ababa, Ethiopia

Abstract: BackgroundMother-to-child transmission (MTCT) of human immunodeficiency virus (HIV) remains the major source of HIV infection in young children. Targeting pregnant women attending antenatal clinics provide a unique opportunity for implementing prevention of mother-to-child transmission (PMTCT) programmes against HIV infection of newborn babies. This study aimed to investigate factors associated with the acceptability and utilization of PMTCT of HIV.MethodsAn institution based cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
56
7
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 22 publications
10
56
7
1
Order By: Relevance
“…In this study about three quarter (76.2%) pregnant mothers underwent HIV testing on current pregnancy and this finding was in in line with a study in Ghana (76%) [14], Cambodia (76%) [15] and it was lower than the studies conducted in Northwestern Ethiopia at Gondar town (82.5%) [10], in a capital city of Ethiopia, Addis Ababa town (94%) [12], in South Ethiopia at Hawassa Referral Hospital (96%) [16], Southern Ethiopia (100%) [17] and Northern Tanzania (98%) [18]. The possible reasons for increment in prior studies might be using of health institution based study [10,12,[16][17][18] since pregnant mothers having positive attitude and better awareness may visit health institution and tested for HIV and in studies [10,12,16,17] the study participants were living in town thus they can easily access the information about VHCT and health services for test. The current finding of VHCT uptake was also having slight increment when compared with a studies in Northwest Ethiopia (72.0%) [9], Kumasi in Ghana (73.0%) [19], Komfo Anokye Teaching Hospital in Ghana (73.9%) [20], hospital ANC clients in western Kenya (68%) [21], Uyam District in Nigeria (55.7%) [22], Botswana (54%) [23], and Oman (51.9%) [24].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study about three quarter (76.2%) pregnant mothers underwent HIV testing on current pregnancy and this finding was in in line with a study in Ghana (76%) [14], Cambodia (76%) [15] and it was lower than the studies conducted in Northwestern Ethiopia at Gondar town (82.5%) [10], in a capital city of Ethiopia, Addis Ababa town (94%) [12], in South Ethiopia at Hawassa Referral Hospital (96%) [16], Southern Ethiopia (100%) [17] and Northern Tanzania (98%) [18]. The possible reasons for increment in prior studies might be using of health institution based study [10,12,[16][17][18] since pregnant mothers having positive attitude and better awareness may visit health institution and tested for HIV and in studies [10,12,16,17] the study participants were living in town thus they can easily access the information about VHCT and health services for test. The current finding of VHCT uptake was also having slight increment when compared with a studies in Northwest Ethiopia (72.0%) [9], Kumasi in Ghana (73.0%) [19], Komfo Anokye Teaching Hospital in Ghana (73.9%) [20], hospital ANC clients in western Kenya (68%) [21], Uyam District in Nigeria (55.7%) [22], Botswana (54%) [23], and Oman (51.9%) [24].…”
Section: Discussionsupporting
confidence: 90%
“…The frequently mentioned reason for not up taking VHCT service in this study was fear of stigma and discrimination both in qualitative and quantitative (40.9%) results. This finding was supported by studies in Northwest Ethiopia [9,11] and other studies [9,12,22,16,17,[25][26][27][28]. The reason of no tested for HIV in about 63.5% pregnant mothers in North-West Ethiopia was fear of rejection by the community if result become positive [9].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previously, HIV‐affected couples were stigmatized for having or desiring children, but acceptance has grown because the risk of transmitting HIV to the child has been greatly reduced by engagement in prevention of mother‐to‐child transmission (PMTCT) programs. The HCPs noted that if an HIV‐affected woman is provided with information on antiretroviral therapy and PMTCT, she will be more likely to have a positive attitude toward having a healthy, HIV‐uninfected child . They also reported that HIV infection does not change reproductive desires, which are influenced by multiple factors including the number of children the woman already has, time since HIV diagnosis, current health status of the HIV‐infected individual, age, and disclosure of the HIV‐positive status to the sexual partner …”
Section: Discussionmentioning
confidence: 99%
“…PMTCT service utilization was influenced by different factors. Studies revealed that factors associated with the uptake of PMTCT services are knowledge and attitudes of mothers on HIV, stigma and discrimination, male partner involvement, disclosure of HIV status, quality of the service, health workers approach, access to and availability of PMTCT services, and educational status of the women [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%